Entropy generation and natural convection of nanofluids in a trapezoidal cavity having an innersolid cylinder - Ishak M.S.; Alsabery A.I.; Hashim I. (IOP Publishing Ltd, 2023)
Alumina; Aluminum oxide; Entropy; Finite difference method; Isotherms; Nanofluidics; Natural convection; Numerical methods; Bejan number; Bottom wall; Control parameters; Entropy generation; Isentropic; Rayleigh number; Solid cylinders; Trapezoidal cavity; Cylinders (shapes)